Sexual Assault Prevalence and Community College Students: Challenges and Promising Practices. (June 2020) - J. Potter, Sharyn; Fox, Nicole; Smith, Delilah; Draper, Nora; Moschella, Elizabeth A.; Moynihan, Mary M.
Recently, much research has been dedicated to understanding how to prevent and address the aftermath of sexual assault (SA) on traditional 4-year college and university campuses in the United States. However, less scholarly attention has been paid to 2-year institutions, commonly known as community colleges. This review illuminates the different situational contexts faced by community college students, compared with students at 4-year colleges. These differences are shaped by community college characteristics, student demographics, and geographic location of their students. Community colleges enroll a higher percentage of women, first-generation students, and low-income students than 4-year colleges. Furthermore, community colleges are academic homes to the most racially and ethnically diverse student population, with higher numbers of African Americans, Latinos, immigrants, and nonnative English speakers. These populations (e.g., women, racial minorities, first-generation, low-income) are at a greater risk for SA; yet, 2-year institutions have less funding and resources available to address SA on their campuses. Thus, this article reviews the problem of campus SA on community colleges and highlights the challenges that 2-year institutions face in comparison with those that 4-year institutions face when implementing SA prevention and response strategies. Then, a case study of a 3-year project on one nonresidential and seven community colleges is presented, which illustrates how 2-year institutions can forge relationships with community professionals to address SA on their campuses.